Fonolito como fonte alternativa de potássio na cultura da cana-de-açúcar - Montes, Rafael Marangoni (2022)
Brazil, one of the world's main producers of food, fiber and energy, is highly dependent on imported inputs for the production of its crops, mainly fertilizers. Of the amount of fertilizers used by Brazil in 2021, 85% came from imports, showing the high dependence that the country has. Oscillations in the prices of these inputs, as well as their availability, directly affected national stability. With the objective of investigating the potential use of the phonolite from Poços de Caldas-MG, as a source of potassium, two experiments were set up at field level, with sugarcane cultivation. In the municipality of Campo Florido-MG, an experiment was set up with cane plants, variety CTC 9002, in a Dystrophic Red-Yellow Latosol with low potassium concentration, evaluating doses (60, 120 and 240 kg ha-1 of K2O) and potassium sources (phonolite, phonolite with potassium chloride (KCl) and KCl). The second experiment was installed in the municipality of Veríssimo-MG, using the CTC 4 variety, in a dystroferric Red Latosol with low potassium concentration, evaluating doses (60, 120 and 240 kg ha-1 of K2O) and sources of potassium (phonolite and KCl) in second-cut ratoon cane. Despite not having been observed significant differences for the sources, it is observed that the phonolite and the phonolite with KCl, in the first experiment, and the phonolite, in the second experiment, presented equivalent results to the KCl in relation to the foliar concentrations of K, Na, Si, Cu, Fe, Mn, Zn, culm productivity, total recoverable sugar and sugar productivity, both for plant and ratoon cane. Potassium fertilization provided an increase in stalk productivity, ATR and sugar productivity, both in the direct effect, as well as for the residual effect and the cumulative effect. In the second experiment, the phonolite provided an increase in silicon and potassium concentrations in the soil after 2 years of sugarcane cultivation.